2012
DOI: 10.1002/sia.4998
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, atomic structure, and bonding variation at TiN/VN interface by chemical segregation

Abstract: Introduction of alloying elements often alters properties of materials. In the technologically significant multilayered superlattice coatings, interfaces are known to play a key role in the deformation mechanisms, especially in the phenomenon of interfaceinduced superhardness at nanoscale. Here, we elucidate, by first-principles calculations, atomic structure of TiN/VN interface and its relationship to adhesion upon introducing Cr, Mo, Ta, Y, Al, Nb, Zr, and Sc, the very commonly occurring alloying elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…To date, great efforts have been made both in experiment 1,3 and simulation [4][5][6][7] to clarify the mechanism of the superhardness of TiN/VN nano-multilayered coatings. For example, Kim et al 3 proposed an equation to describe hardness of composites, and compared it with that determined by a nanoindentation test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, great efforts have been made both in experiment 1,3 and simulation [4][5][6][7] to clarify the mechanism of the superhardness of TiN/VN nano-multilayered coatings. For example, Kim et al 3 proposed an equation to describe hardness of composites, and compared it with that determined by a nanoindentation test.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim et al 3 proposed an equation to describe hardness of composites, and compared it with that determined by a nanoindentation test. Yin et al 4,5 applied the rst-principles calculation to investigate the electronic property, bonding conguration and adhesion at TiN/VN interface as well as the tensile and fracture process. 7 Although these studies help to understand the interfacial structures, they do not consider the effect of defects.…”
Section: Introductionmentioning
confidence: 99%
“…8 Even though these materials individually show advantageous properties, a composite structure, such as a multilayer type, can exhibit improved performance compared with TiN and VN monolayers, due to the appearance of interfaces and the contribution of each compound to the emergent behavior of the entire multilayer system. 9 In the specific case of coating hardness, the improvement of this property, with a two nitride multilayer approach, is related to two main mechanisms 10 : (i) the different elastic moduli of the constituent materials 11 and (ii) the formation of coherency strains near the interfaces, 12 as a consequence of the formation of coherent interfaces 13,14 in superlattices. Helmersson et al 10 reported a hardness of $56 GPa for the VN/TiN multilayer system, benefitting from the two aforementioned mechanisms.…”
mentioning
confidence: 99%
“…The effect of these two mechanisms is the reduction of dislocation mobility which, for the case of VN/TiN multilayers, is based on the similarity of the crystal structures of the nitrides formed with these two metals (Ti and V). This leads to the formation of coherent interfaces, 9,14 which are regions that prevent grain boundary sliding and block dislocation propagation. 15,16 These cited works, featuring the hardness improvement of the VN/TiN multilayer system, have focused mainly on single-crystal superlattice heterostructures, with less studies having been carried out for coatings in a nanocrystalline state.…”
mentioning
confidence: 99%